The Silent Struggle: Early Paternal Loss and Its Influence on Adolescent Self-Esteem - Rossall, Carlo Amadeo; Arianti, Rudangta (Journal of Psychological Perspective, 2025)
Over the years, children who do not have a father figure has become a widely discussed topic. The absence of a father figure, which can be caused by death, criminal punishment, neglect, or limited amount of contact such as divorce. Previous studies have explored self-esteem in adolescents who have lost a father figure, but specifically since what age hasn’t recently been studied enough. Therefore, this research’s participants will focus on adolescents who have lost a father figure since an early age, precisely between the ages of 0 – 6 years. A qualitative approach and phenomenological method were used with the aim of presenting a picture and explanation of the phenomenon, and due to the specific criterias, purposive sampling technique would be most ideal to obtain participants for this research. Results of this study emerged four major themes, each with its own additional points. Struggles of fatherlessness elaborates on the challenges and struggles that occur from this phenomenon, including identity dilemma, and the feeling of missing a form of paternal attachent. Acceptance tells the process of accepting one's condition, which automatically differentiates them from people in general with complete parents. Independence and control describe the dynamics that participants go through regarding control over their personal lives due to the dominance and expectations of their mother after losing the father figure in a household. Self-assurance explains how participants deal with the challenges from the loss of their father figure.